Preliminary value chain analysis of gum and resin marketing in Ethiopia - Kassa, H.; Tefera, B.; Fitwi, G. (Center for International Forestry Research, 2011)
The production of gums and resins in Ethiopia falls far short of its potential, even though the export volume and revenue from these dry-forest products have significantly increased during the past decade. However, consistently low prices mean producers have little economic incentive to manage dry forests responsibly. Actions are required at various levels to enable both the country and producers to obtain better prices for gums and resins. Ethiopia’s federal and state governments must work on product and market development, which will require data on the production and marketing aspects of the gums and resins subsector. This policy brief presents findings of studies conducted in 2007 and 2010 with the aim of filling knowledge gaps in the long-term trends of production and marketing and the current status of the value chain, focusing mainly on the structure, conduct and performance of natural gums and resins marketing in Ethiopia. The studies focussed on Tigray type gum olibanum (frankincense), which accounts for more than 90% of the export volume of gums and resins. To assess trends in production and marketing, secondary data were gathered and analysed. The Structure Conduct Performance (SCP) framework of value chain analysis was adopted, and data were collected using rapid market appraisal, where key informants and market actors along the chain were interviewed. Findings indicate that the volumes of gums and resins produced and marketed over the years are characterised by inconsistency. During the past 5 years, however, the total volume of exports has risen sharply. During the past 10 years, domestic and export markets accounted on average for about 40% and 60% of the total marketed volume, respectively. The share of producers from the marketing margin of gums and resins ranged from 19% to 75%, and tended to be lower than that for exporters and wholesalers, particularly when the marketing channels are long and producers are not organised in cooperatives. For example, producers’ marketing margin for Tigray type frankincense was 34.5% in 2007 and 19.1% in 2010, compared with 41.1% and 31.4%, respectively, for exporters or wholesalers. It is necessary to improve the efficiency of the market for producers and increase their share of the profits if they are to have an economic incentive to responsibly manage dry forests, which have vital environmental and ecological benefits for Ethiopia. Encouraging producers to form cooperatives and exporters to form an association is suggested as one way to increase their capacity for producing more and better-quality products, to add value to raw products and to boost their bargaining power. Studying options for appropriate governance of access to resources and the marketing chain is recommended in order to create economic incentives for producers to manage dry forests responsibly